The torture papers: The road to Abu Ghraib - Greenberg, Karen J (Cambridge University, 2013)
The Torture Papers consists of the "torture memos" and reports written by U.S. government officials to prepare the way for and to legitimize coercive interrogation and torture in Afghanistan, Guantánamo, and Abu Ghraib. This volume of documents presents for the first time a compilation of materials that prior to publication have existed only piecemeal in the public domain. The Bush Administration, concerned about the legality of harsh interrogation techniques, understood the need to establish a legally viable argument to justify such procedures. The memos and reports in this volume document the systematic attempt of the U.S. government to prepare the way for torture techniques and coercive interrogation practices, forbidden under international law, with the express intent of evading legal punishment in the aftermath of any discovery of these practices and policies.